The Effect of Talent Management and Perceived Organizational Support on Employee Retention Mediated by Organizational Commitment - Susan Sabrina Sitaniapessy; Armanu Armanu; Desi Tri Kurniawati (Ridwan Institute, 2023)
This study examines the effect of talent management and perceived organizational support on the employee retention at Bank Jatim KC Kepanjen through mediating organizational commitment. This study uses saturated sampling. Primary data was obtained by distributing questionnaires to 143 employees. Data analysis used partial least square (SEM-PLS) structural equation modeling with Smart-PLS 3.0 application. The results show that talent management had no significant effect on employee retention and perceived organizational support had a positif and significant effect on employee retention. This study also found that organizational commitment is able to mediate the effect of talent management and perceived organizational support on employee retention. From these findings, it was concluded that talent management is not able to significantly increase employee retention but talent management is able to increase employee retention through increased organizational commitment. Furthermore, increasing perceived organizational support can improve employee retention.